Pengembangan Media Flipbook E-MODEMA Untuk Meningkatkan Membaca Pemahaman Siswa SD Kelas IV Pada Pembelajaran Bahasa Indonesia - Elvona Agasthi Natarina Sanjaya; Desvita Maharani; Riska Ayuk Cahayani; Rani Setiawaty (Jurnal Inovasi Pendidikan Madrasah Ibtidaiyah, 2025)
This study was motivated by the low reading comprehension skills offourth grade students of SD 4 Karangbener, especially in understandinglegend texts in Indonesian language learning. One of the main causes isthe low interest in reading and the limited availability of interactive and contextual learning media. Therefore, this study aims to develop digitalflipbook media called E-MODEMA (E-Module of Legendary StoriesBased on Demak Local Wisdom) as an effort to improve students' readingcomprehension skills. This study used a Research and Development(R&D) approach using the ADDIE development model (Analysis, Design,Development, Implementation, and Evaluation). The test subjectsconsisted of 5 fourth grade students and several teachers as validators.The instruments used in this study include: (1) expert validationquestionnaire that assesses the appearance and content aspects, (2) pre-test and post-test questions to measure effectiveness, (3) observationsheets, (4) structured interviews, and (5) teacher and student responsequestionnaires to assess the attractiveness and usefulness of the media.The results of the pre-test and post-test showed a significant increase withan N-gain value of 0.73 which is included in the high category. Studentsgave a positive response with a percentage of interest of 82%, and theteacher gave an assessment of 92%. Based on these results, E-MODEMAflipbook media is declared effective in improving students' readingcomprehension once a week.